Labor standards and social conditions in free trade zones: The case of the Manaus free trade zone - Louisiana Cavalcanti Teixeira (Kiel Institute for the World Economy (IfW), 2019)
The creation of the Manaus Free Trade Zone had a development purpose in the Brazilian political, economic and social scenario between 1960 and 1970. This industrial pole was an important device in achieving the desired development, populating a region considered deserted and exposed to external threats at that time. It has guaranteed the improvement on labor standards and social conditions in the Manaus' district and has become the main driving force behind regional employment, higher salaries and growth over the past decades. Using the residuals and the stochastic frontier techniques to estimate the labor and social performances of the Manaus Free Trade Zone, the analysis confirms that the implementation of the special economic zone collaborated to labor and social efficiency in the area - compared to other important industrial Brazilian municipalities - due to the rigid checks conducted by SUFRAMA and the strict respect of labor standards applied in the MFTZ. Nevertheless, economic linkages in the region are still weak and positive spillovers from Manaus to its surroundings were probably inexistent.
Keywords: F12; F13; F14; 330; free trade zone; Manaus; employment; labor standards; social progress